The effect of marital status and qualifications on the dangers of psychological work of plant science and science education lecturers - Ugwuanyi, Samson; Ugwuanyi, Christian S. (Universitas Negeri Padang, 2022)
Because of the multicultural nature of Nigerian schools, most employees, particularly teachers, are exposed to one or more psychological hazards at work. In Nigeria, psychosocial work hazards are frequent, but no research has been done to see how lecturers' demographics affect their psychosocial work hazards. As a result, the impact of marital status and qualification on the psychological work hazards of plant science and science education lecturers was investigated in this study. The study used a quantitative research approach and an ex-post fact research design with a sample of 87 teachers from the University of Nigeria, Nsukka. The researchers adapted a 28-item questionnaire on work deviant behaviour to collect data for the study. The questionnaire items have internal consistency reliability of 0.76. Mean and analysis of variance were used to analyze the data. The study's findings demonstrated that lecturers' marital status and qualifications had no bearing on their psychological work hazards. This suggests that the marital status and qualification of lecturers are not significant factors in their psychosocial work hazards. As a result, it was recommended that university authorities be equitable in their handling of psychosocial work hazards of lectures, taking into account their marital status and qualification.